Evaluation of an Improved Technique for Geosynthetic-Reinforced and Pile-Supported Embankment - Jun Zhang; Shao-wen Liu; He-fu Pu (Advances in Materials Science and Engineering, 2015)
With a large number of applications of conventional technique for geosynthetic-reinforced and pile-supported (GRPS) embankment (called CT embankment), many deficiencies have been exposed. In view of the deficiencies, an improved technique, fixed-geosynthetic-reinforced and pile-supported embankment (called FGT embankment), is developed. To investigate the performance of the FGT embankment, the comparison analyses and parametric studies are conducted by Finite Element Method (FEM). The influencing factors investigated include elastic modulus of soil, tensile stiffness of geosynthetics, pile length, pile spacing, and pile elastic modulus. In addition, the cost evaluation for the FGT embankment and CT embankment is also made. The results show that the FGT embankment can significantly reduce the settlement and differential settlement, enhance the stability, and provide an economical and effective measure for the construction of high embankment at the bridge approach.